Das Potenzial von Feedback als Form der Lehrer-Schüler-Interaktion bei der Entwicklung der kommunikativen Sprachkompetenz – der aktuelle Forschungsstand - Janicka, Monika (Neofilolog, 2017)
The contemporary learning culture perceives learners as active and aware participants in the learning process. This implies a new understanding of interactions in the classroom. The present paper is focused on feedback as a special type of teacher-learner interaction and its potential for cognitive activation of learners and constructive enhancement of individual learning processes. Feedback which activates learners and increases the amount of the input and output in the foreign language is able to enhance students` communicative language competence. The article discusses the changing role of feedback referring to the current state of research.